Factors associated with childbirth self-efficacy: a multicenter cross-sectional study in China. (February 2021) - Zhao, Yuxin; Wu, Jianxiong; Yang, Heping; Yin, Xiaoxv; Li, Dandan; Qiu, Lei; Sun, Na; Gong, Yanhong
Abstract: Objective: Childbirth self-efficacy is an important indicator of a woman's choice of mode of delivery, and has been found to be closely related to adverse perinatal outcomes. This study was conducted to evaluate childbirth self-efficacy and its influencing factors among pregnant Chinese women. Design: A multicenter cross-sectional study. Methods: Pregnant women were recruited by using a convenience sample in four maternal and child healthcare hospitals, one each from four cities in China between May and June 2018. Women with a singleton pregnancy, aged 18 years and older, and able to read and write the Chinese language were included. Trained investigators used a structured self-administrated questionnaire to collect data. EpiData 3.1 was used to prepare the database, and SAS 9.2 was used for statistical analysis. A one-way ANOVA test or independent sample t-tests were used to test the between-group differences in childbirth self-efficacy scores, as appropriate. Multivariate linear regression analyses were conducted to examine childbirth self-efficacy of the pregnant women, and the socio-demographic and obstetric factors that influence childbirth self-efficacy. Findings: A total of 1, 796 pregnant Chinese women with singleton pregnancies were recruited into this study. The average childbirth self-efficacy score of the participants was 14.42 (standard deviation = 2.80); 9.35% of the participants scored ≤ 10 points, while 22.49% got more than 15 points. Multivariate linear regression analysis revealed that higher childbirth self-efficacy was significantly associated with younger age ( ß  = -0.05, P <0.01), lower body mass index (BMI) ( ß  = -0.06, P <0.01), receiving prenatal education ( ß  = 0.47, P <0.01), performing physical activity 6-7 times per week ( ß  = 0.47, P  = 0.03), and fair ( ß  = 0.57, P <0.01) or good ( ß  = 1.08, P <0.01) self-rated health status. Key conclusions and implications for practice: Childbirth self-efficacy was low among pregnant Chinese women. Women with older age, higher BMI, and worse self-rated health status had lower childbirth self-efficacy. On the other hand, women who frequently exercised, had some prenatal education, and had better self-rated health showed higher childbirth self-efficacy during pregnancy. Interventions concentrating on improving childbirth self-efficacy in China should focus on prenatal education for expectant mothers, and more attention should be given to pregnant women who are older, obese, are less physically active, and are in poor health.